Investigating the effect of Sense of place to the place and quality of green spaces in urban branding (Case study: Tabriz metropolis) - Nazli pakru; Dariush Sattarzadeh; Lida Bolillan; Mir Saeed Mousavi (تحقیقات کاربردی علوم جغرافیایی)
In order to achieve a sustainable competitive advantage to overcome the prevailing have been proposed competition between cities, various strategies; Urban branding is one of these strategies. Urban branding is considered as an important asset in the development of the city as well as an effective tool to differentiate, improve the position and increase the influence and prestige of the city. This study was conducted to investigate the effect of the Sense of place and quality of green spaces in urban branding. The present study is applied in terms of purpose and descriptive-analytical in terms of method. In order to collect the required data and information, library and field methods and questionnaire tools were used. The statistical population of the study consists of citizens living in Tabriz; the sample size was estimated 384 people using Cochranchr('39')s formula. SPSS and Lisrel software were used to analyze the data. The results showed that the Sense of place and quality of urban green spaces has a positive and significant effect on urban branding. It was 0.37. According to the value of the obtained path coefficient, the effect of the Sense of place is greater than the quality of urban green space in urban branding.